Journalism on migration with a rights approach Methodological dialogues between Human Rights and Folkcommunication (Revista Internacional de Folkcomunicação, 2020)
The work delves into the construction of a journalistic discourse that incorporates and actively uses the human rights perspective in media work that thematizes the migratory phenomenon and migrants as news objects or contexts. Concerns about the way in which migrants are represented and the migratory phenomenon is addressed in the Latin American media is based on the identification of persistent processes of inequality in the possibilities of symbolic construction, which negatively affect the image of migrants and take away the possibility of their own voice in the hegemonic media. In this sense, Folkcommunication and human rights recover this discussion and provide valuable tools to reconfigure contemporary journalistic practice. The work analyzes the way of construction of journalistic discourses using the conceptual and methodological approach of human rights, as well as incorporating tools of discourse analysis from a communication perspective. As a result of the critical survey carried out, elements of approach and concrete recommendations are elaborated to reconfigure the practice and journalistic production on migration based on a human rights framework. Journalism; Migrants; Human Dights; Communicative inequality; Representations.